Review Article: Pharmacological Activities of Red Spinach (Amaranthus tricolor) - Hasyimi, Meifia; Iqbal, Muhammad; Andrifianie, Femmy; Triyandi, Ramadhan (Medula, 2025)
Red spinach (Amaranthus tricolor) is a leafy vegetable known for its distinctive red or purplish leaves. This plant is widely cultivated as its leaves are edible and packed with essential nutrients beneficial to the body. Red spinach is rich in antioxidants such as beta-carotene and vitamin C, along with vital minerals like iron, calcium, magnesium, phosphorus, and potassium, which support overall health. Regular consumption of red spinach is believed to improve blood circulation, boost immunity, prevent anemia, accelerate wound healing, and promote bone health due to its comprehensive nutritional content. This article aims to review the pharmacological activities of red spinach based on literature from credible sources such as Google Scholar, Garuda, Neliti, and Sinta, focusing on publications within the past five years. The review findings reveal that red spinach possesses various potential pharmacological properties. These include antioxidant activity, anemia treatment, reduction of liver enzymes such as SGOT and SGPT, improvement of liver function, and enhancement of metabolic processes. Additionally, red spinach is recognized for its benefits in maintaining facial skin health, suggesting its potential as a natural ingredient in skincare products. Therefore, red spinach is not only a nutritious vegetable but also holds promise as a natural herbal remedy with therapeutic potential for the future.